2023
DOI: 10.1038/s41396-022-01355-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene loss and symbiont switching during adaptation to the deep sea in a globally distributed symbiosis

Abstract: Chemosynthetic symbioses between bacteria and invertebrates occur worldwide from coastal sediments to the deep sea. Most host groups are restricted to either shallow or deep waters. In contrast, Lucinidae, the most species-rich family of chemosymbiotic invertebrates, has both shallow- and deep-sea representatives. Multiple lucinid species have independently colonized the deep sea, which provides a unique framework for understanding the role microbial symbionts play in evolutionary transitions between shallow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 98 publications
1
43
0
Order By: Relevance
“…Thiodiazotropha spp. analyzed by Osvatic et al (2023). A maximum-likelihood phylogenetic tree using a 400 universal marker genes database was performed in PhyloPhlAn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiodiazotropha spp. analyzed by Osvatic et al (2023). A maximum-likelihood phylogenetic tree using a 400 universal marker genes database was performed in PhyloPhlAn.…”
Section: Resultsmentioning
confidence: 99%
“…Publicly available genomes from all species from the Sedimenticolaceae family, according to GTDB R07-RS207, and all Candidatus Thiodiazotropha genomes from the Osvatic et al (2023) study were retrieved from NCBI. A full list and characteristics of genomes used for this analysis is found in Supplementary Table S11.…”
Section: Analysis Of Root Microbiomes From Contrasting Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene gain and loss are essential adaptive strategies employed by many fungi to respond to novel environmental stressors (Osvatic, et al 2023). To investigate gene loss in the OAc lineage, 524 orthologs were identified that were present in Clade 1 (Figure 3A) but absent in the OAc annotation (Figure 3A).…”
Section: The Ophiocordyceps Associate Of Part Corni Has Undergone Gen...mentioning
confidence: 99%
“…The isotopic composition of each sample was expressed as the relative difference between isotopic ratios in the sample and that in conventional standards (Vienna Pee Dee Belemnite, atmospheric N2 and Canyon Diablo Troilite for carbon, nitrogen and sulfur, respectively). Measured isotope ratios are reported in the δ per mille (‰) notation representing the deviation from the standards: δ Sample = ( RSample /Rstandard − 1 ) ×10 3 where, R = 15 N/ 14 N, 13 C/ 12 C or 34 S/ 32 S ratios.…”
Section: Sample Collectionmentioning
confidence: 99%